2017
DOI: 10.3389/fpubh.2017.00347
|View full text |Cite
|
Sign up to set email alerts
|

Survey on the Use of Whole-Genome Sequencing for Infectious Diseases Surveillance: Rapid Expansion of European National Capacities, 2015–2016

Abstract: Whole-genome sequencing (WGS) has become an essential tool for public health surveillance and molecular epidemiology of infectious diseases and antimicrobial drug resistance. It provides precise geographical delineation of spread and enables incidence monitoring of pathogens at genotype level. Coupled with epidemiological and environmental investigations, it delivers ultimate resolution for tracing sources of epidemic infections. To ascertain the level of implementation of WGS-based typing for national public … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
100
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(105 citation statements)
references
References 22 publications
3
100
0
2
Order By: Relevance
“…The study of virulence factors was particularly important for E. coli, as also observed by Revez and colleagues (Revez et al, 2017), while WGS-serotyping as well as the detection of resistance genes were mostly used for characterising Salmonella spp. and E. coli isolates.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The study of virulence factors was particularly important for E. coli, as also observed by Revez and colleagues (Revez et al, 2017), while WGS-serotyping as well as the detection of resistance genes were mostly used for characterising Salmonella spp. and E. coli isolates.…”
Section: Discussionmentioning
confidence: 85%
“…VTEC, Campylobacter spp., L. monocytogenes, Coagulase Positive Staphylococci, others) and antimicrobial resistant isolates from animals, food, feed and their environment. Similar surveys have also been launched by ECDC to collect information from the European public health sector laboratories (Revez et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many recent evaluations on the use of NGS for the determination of AMR have emphasised the difficulty of establishing a curated knowledge base on drug resistance genetic determinants to be used as a reference database in NGS data analysis 2, 13, 55 . The same problem is mirrored in the design of a benchmark that would ensure all determinants are correctly detected.…”
Section: The Challengesmentioning
confidence: 99%
“…Focusing on the bioinformatics step, an important shared challenge is the need to correctly and reliably identify the known genomic determinants of AMR from a set of NGS reads produced from sequencing a sample. The ECDC study reported the requirement for sufficient bioinformatics expertise as one of the important hurdles to a more general implementation of NGS for routine testing 2 . This observation has also been expressed in recent case studies and reviews 711 .…”
Section: Introductionmentioning
confidence: 99%